Cation‐/Anion‐Based Physicochemical Mechanisms for Anodically Coloring Electrochromic Nickel Oxide Thin Films. Issue 7 (20th January 2022) - Qu, Hui‐Ying; Wang, Xiyang; Chen, Ding; Bai, Zhihao; Wang, Nannan; Zhu, Yan‐Qiu; Tong, Zhangfa; Ji, Hongbing; Niklasson, Gunnar A.
Abstract: The rapidly expanding field of intelligent ion‐based devices has increased interest in the use of anodically‐coloring electrochromic nickel oxide thin films. The degradation and coloration mechanisms of nickel oxide, especially in Li + ‐based electrolytes, are yet to be well understood. Herein we demonstrate that high potentials have a positive effect on the electrochromic performance of nickel oxide thin films. Our studies show that Cl − ions involved in the electrochromic process have been accumulated on the surface of the films upon extended electrochemical cycling, as confirmed by the X‐ray Photoelectron Spectroscopy. X‐ray Absorption Spectroscopy results indicate that the formation of Ni−Cl bonds influence the structural distortion and that the hybridization between Ni 3d and O 2p orbitals has been enhanced. Density functional theory calculations provide further insights for the band structures and how they change when Li + and Cl − are adsorbed. Our results have revealed the underlying physical and chemical origins associated with the coloration mechanism and the degradation of nickel oxide thin films and highlighted the key role of Cl − . These new understandings will advance the development of superior electrochromic materials and the designing of efficient and durable electrochromic devices, both experimentally and theoretically. Abstract : Changing colors : Cl − and Li + are involved in the electrochromic process of nickel oxide when cycled in an electrolyte of 1 M LiClO4 ‐PC. These ions adsorb onto the surface of nickel oxide and are accumulated upon extended electrochemical cycling. Adsorption of Cl − takes place at high potentials and leads to darkening of NiO, while bleaching at lower potentials happens via the desorption of Cl − and/or adsorption of Li + .